High responsivity of Gr/ n-Si Schottky junction near-infrared photodetector. (February 2021) - Tang, Yuling; Chen, Jun
Abstract: Si PN junction (p-Si/n-Si) photodetectors have been widely used in the near-infrared band. In this paper, the original p-Si is replaced by graphene to form a Gr/n-Si Schottky junction photodetector. Due to the excellent photoelectric properties of graphene, the incident light can irradiate the depletion region of the Schottky junction to generate more photo-generated carriers and has a higher barrier height, which corresponds to large electric field, and accelerates the photogenerated carriers to the electrodes, resulting in the effective collection of photogeneration of charges. The experimental results show that the Gr/n-Si Schottky junction photodetector has better performance. Under the illumination of 808 nm laser lamp, the I–V characteristic of the device was measured, the dark current of Gr/n-Si Schottky junction photodetector has reduced by two orders of magnitude, while the photocurrent was improved, the barrier height reaches 0.938 e V, and the quantum efficiency increases to 71%. Besides, the light responsivity and detectivity are significantly improved to about 0.456 A / W and 7.96 × 10 11 c m H z 1 / 2 W − 1 compared with the p-Si/n-Si photodetector. Highlights: The Graphene/n-Si Schottky junction photodetector was fabricated and compared with p-Si/n-Si photodetector. The infrared light responsivity and detectivity of the Graphene/n-Si photodetector have been greatly improved. The barrier heights of p-Si/n-Si interface and Graphene/n-Si interface were calculated to explain the performance improvement.